Identification of the HERV-K gag antigen in prostate cancer by SEREX using autologous patient serum and its immunogenicity - Ishida, Toshiaki (Academy of Cancer Immunology, 2008)
The prostate cancer HERV-K gag-related NGO-Pr-54 antigen was identified by SEREX analysis using autologous patient serum. NGO-Pr-54 mRNA was observed to be faintly expressed in normal prostate and strongly expressed in a variety of cancers, including ovarian cancer (5/8), prostate cancer (6/9), and leukemia (5/14). A phage plaque assay showed that a strong reaction was constantly observed with clone ZH042 in which the 5' end of NGO-Pr-54 is deleted, suggesting that it contained the sequence coding for the protein product. A TI-35 mAb was produced using a recombinant protein (438 aa) deduced from the sequence of ZH042. Transfection of clone ZH042 into 293T cells resulted in the production of an approximately 50-kDa molecule visualized by Western blotting. Natural production of the molecule was confirmed in a SK-MEL-23 melanoma cell line. An indirect immunofluorescence assay showed that NGO-Pr-54 protein was expressed on the cell surface as well as in the cytoplasm. Cell surface expression was confirmed by flow cytometry using the TI-35 mAb. The antibody response against NGO-Pr-54 was observed in patients with bladder (5.1%), liver (4.1%), lung (3.4%), ovarian (5.6%), and prostate (4.2%) cancer, as well as with malignant melanoma (13.2%).